PENGEMBANGAN DIGITAL MARKETING DALAM MENINGKATKAN KOMERSIALISASI USAHA BATIK KEMBANG TURI - Sunandes, Aris; Zamrodah, Yuhanin; Puspitorini, Palupi; Lisaria Putri, Rumanintya (Universitas Islam Balitar, 2022)
This study aims to analyze the development of digital marketing in increasing the commercialization of the Kembang Turi Batik business in the Turi Village, Sukorejo District, Blitar City. The research method uses descriptive qualitative data collection by interviewing, observing and focus group discussions. The findings obtained are that the implementation of digital marketing is not optimal because it only relies on social media. The application of digital marketing is carried out with the stages of literacy, training and development then application of programs that are in accordance with the conditions of the Kembang Turi Batik group. The results of the research are training in developing web-based e-Commerce information technology facilities and optimizing social media for craftsmen, training to increase the strong branding of batik products produced, so that with this it is hoped that craftsmen can expand marketing by promoting their products through various social media which is owned by batik kembang turi, so as to increase the income and welfare of the craftsmen.